Quench dynamics in bare YBCO thin films with and without artificial pinning centers - Mejia, Samuel; Aye, Moe; Huhtinen, Hannu; Paturi, Petriina (Institute of Physics Publishing, 2026)
In this study, we investigate the differences in the normal zone development between artificial pinning center free (APC-free) and BaZrO3 (BZO)-doped YBa2Cu3O (YBCO) thin films deposited on SrTiO3 substrates. Normal zone propagation velocities (NZPV) and minimum quench energies (MQE) were measured over a wide range of temperatures (20–70 K) and magnetic fields (0–8 T) as a function of the percentage of the critical current (%). We found that lower MQE values are required in BZO-doped YBCO to trigger a quench. The most significant differences between APC-free and BZO-doped films in NZPV behavior were observed at high temperature and magnetic field values. Differences in quench characteristics can be attributed to variations in flux pinning mechanisms and current-carrying capabilities arising from the distinct properties of pinning centers. Through detailed analysis, this study enhances the understanding of how flux flow influences normal zone development in different YBCO thin films, providing insights relevant to technological challenges such as stability under high magnetic fields and quench detection in future high-temperature superconductor magnets.